A Second-Order Two-Scale Algorithm for Thermo-Mechanical Coupling Problems in Quasi-Periodic Porous Materials (Communications in Computational Physics, 2018)
This work develops a second-order two-scale (SOTS) model based on homogenization method to predict thermo-mechanical coupling performance of porousmaterials with quasi-periodic structures. For the kinds of porous materials, the corresponding material coefficients are dependent on the macroscopic variable and theradiation effect at microscale is considered in this paper. The quasi-periodic propertiesof the thermo-mechanical coupling models which consider mutual interaction betweentemperature and displacement fields are proposed at first. Then, the two-scale formulas for the thermo-mechanical coupling problems with radiation boundary conditionsare derived successively, and the finite element algorithms based on the SOTS modelare brought forward in detail. Finally, by some typical examples, the effectiveness andvalidity of the proposed algorithms are confirmed. The computational results demonstrate that the SOTS method is efficient and valid to predict the thermo-mechanicalcoupling properties, and can acquire the microscale information of the porous materials accurately.
Keywords: SOTS model; radiation effect; thermo-mechanical performance; quasi-periodic structures.